A giant choledochal cyst: A case reported from Tanzania - Suleiman, Jamil M. (Int J Surg Case Rep, 2021)
INTRODUCTION: Choledochal cyst is a rare common bile duct malformation that usually presents in the pediatric group with abdominal pain, distension, and jaundice. The pathophysiology remains unclear for the cause, and surgery aims to restore biliary enteric drainage. CASE PRESENTATION: We present a six-year-old female who presented with gradual abdominal distention associated with jaundice. Abdominal ultrasound was suggestive of choledochal cyst, and CT-scan confirmed the diagnosis. She was operated on successfully and fared well. CONCLUSION: Choledochal cysts are a rare entity of common bile duct malformations and should be considered as a differential diagnosis in the pediatric age group. Diagnosis can be easily made by non-invasive and in-expensive radiologic modalities like ultrasonography in resource-limited settings.